The Relationship between Iranian Test-Takers’ Reported Strategic Behaviors and Their Test Scores across Different Task Types - Pardis Zafarani (International Journal of Practical and Pedagogical Issues in English Education)
In the realm of language proficiency assessment, understanding the strategies employed by test-takers can provide valuable insights into the complexities of oral proficiency testing. This study delved into the reported strategic behaviors exhibited by Iranian test-takers when tackling integrated and independent speaking tasks within an English oral proficiency examination, while also scrutinizing the connections between these strategic behaviors and test scores. Each of the 28 participants engaged in one independent task and two integrated tasks, subsequently offering insights into the array and patterns of strategies they employed. The findings indicated that integrated tasks elicited a more extensive repertoire of reported strategies compared to independent tasks. Moreover, the integrated tasks demonstrated greater similarity in terms of reported strategy utilization when contrasted with the independent and integrated tasks. In a broader context, the study revealed that the total number of reported strategic behaviors exhibited no significant correlation with total test scores, irrespective of the task type. While these outcomes underscore the value of incorporating integrated tasks into oral proficiency evaluations, as they stimulate increased reported strategy use when multiple language skills are involved, they also underscore the intricate and varied relationships among task type, task performance, and strategy implementation.